A mixed methods study of clinical information availability in obstetric triage and prenatal offices. (18th August 2016) - Meyerhoefer, Chad D; Sherer, Susan A; Deily, Mary E; Chou, Shin-Yi; Peng, Lizhong; Hu, Tianyan; Nihen, Marion; Sheinberg, Michael; Levick, Donald
Abstract : Objective: To determine the effect of availability of clinical information from an integrated electronic health record system on pregnancy outcomes at the point of care. Materials and methods: We used provider interviews and surveys to evaluate the availability of pregnancy-related clinical information in ambulatory practices and the hospital, and applied multiple regression to determine whether greater clinical information availability is associated with improvements in pregnancy outcomes and changes in care processes. Our regression models are risk adjusted and include physician fixed effects to control for unobservable characteristics of physicians that are constant across patients and time. Results: Making nonstress test results, blood pressure data, antenatal problem lists, and tubal sterilization requests from office records available to hospital-based providers is significantly associated with reductions in the likelihood of obstetric trauma and other adverse pregnancy outcomes. Better access to prenatal records also increases the probability of labor induction and decreases the probability of Cesarean section (C-section). Availability of lab test results and new diagnoses generated in the hospital at ambulatory offices is associated with fewer preterm births and low-birth-weight babies. Discussion and conclusions: Increased availability of specific clinical information enables providers to deliver better care and improve outcomes, but some types of clinical data are more important than others. More available information does not always result from automated integration of electronic records, but rather from the availability of the source records. Providers depend upon information that they trust to be reliable, complete, consistent, and easily retrievable, even if this requires multiple interfaces.